Exploring Clinical and Echocardiographic Factors in EHRA Type 2 Atrial Fibrillation for Predicting Ischaemic Stroke: A Search for Unrevealed Insights - Simbolon, Jessica Putri Natalia; Raharjo, Sunu Budhi; Santoso, Anwar; Liastuti, Lies Dina; Hermanto, Dony Yugo; Rossimarina, Vienna; Pritazahra, Armalya; Hanafy, Dicky Armein; Yuniadi, Yoga (The Indonesian Heart Association, 2025)
In “Exploring Clinical and Echocardiographic Factors in EHRA Type 2 Atrial Fibrillation for Predicting Ischaemic Stroke: A Search for Unrevealed Insights” (Indonesian Journal of Cardiology, 44(3), 87-94. https://doi.org/10.30701/ijc.1562), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1562. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error.DOI of original article: https://doi.org/10.30701/ijc.1562